Thermodynamic and economic analysis of ocean thermal energy conversion system using zeotropic mixtures - Yanmei Zhang; Jiawei Deng; Zilong Deng (Case Studies in Thermal Engineering)
Zeotropic mixtures offer a promising strategy for enhancing the thermodynamic efficiency and economic feasibility of ocean thermal energy conversion (OTEC) systems. This study investigates two binary mixtures containing R32: R32/R125 and R32/R134a. Through the development of comprehensive thermodynamic and economic models, the research examines the impact of mass fraction and evaporation temperature on the efficiency and cost-effectiveness of the OTEC system. The results indicate that, especially at high evaporation temperatures, the R32/R134a mixture—characterized by significant temperature glide—substantially increases the total energy production capacity of the OTEC system. Compared to pure R32, the OTEC with R32/R134a (mass fraction of R32 is 0.55) has a net output power increase of 9.87 kW and a reduction in LCOE of about 61.4 %. In addition, the advantages of R32/R125 mixtures over pure working fluids are not significant due to the small glide temperature. Ultimately, this investigation enhances the overall performance of OTEC systems, thereby supporting sustainable energy solutions for island communities.